Investigating the effect of education on man immunodeficiency virus/acquired immune deficiency syndrome preventive behaviors in vulnerable women living in peripheral neighborhoods: Applications of the health belief model - Somayyeh Khazaeian; Ali Navidian; Fariba Shahraki Sanavi; Lila Hadipoor (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Acquired immune deficiency syndrome (AIDS) is a pervasive disease, and its epidemic is spreading around the world. The only way to effectively fight against human immunodeficiency virus (HIV)/AIDS is good-quality health. The present study aimed to investigate the effect of an educational intervention program on HIV/AIDS preventive behaviors based on the Health Belief Model (HBM) in vulnerable women residing in peripheral neighborhoods. MATERIALS AND METHODS: This study was a quasi-experimental research conducted among 200 vulnerable women, randomly selected from four community health centers in peripheral neighborhoods in 2019 in Zahedan, Iran. The data were collected using a researcher-made questionnaire, containing demographic information, HIV knowledge, and the HBM constructs. Besides, the data were collected before, immediately after, and 1 month after the intervention in both groups. Data analysis was performed in SPSS (version 24) using descriptive statistics, Chi-square test, independent t-test, repeated-measures analysis of variance, and multivariate linear regression. RESULTS: The findings revealed no significant difference in the mean scores of knowledge and the HBM constructs before the educational intervention (P > 0.05). However, after the intervention, this difference was significant in three time intervals (P < 0.05). Despite the effectiveness of the educational intervention in the mean scores of knowledge and the HBM constructs in the intervention group compared with the controls, the largest effect size was observed, respectively, in knowledge (d = 0.762) and perceived barriers (d = 0.612), and the smallest effect size was reported in cues to action (d = 0.421). As well, the F-statistic ratio (0.847) demonstrated that the selected demographic variables had failed to explain variations in knowledge mean scores (P = 0.497). CONCLUSION: HBM-based training interventions were positive for HIV/AIDS prevention behaviors. However, training alone does not seem to have enough effect on behavior persistence. Therefore, further research is recommended to investigate the role of predictive factors, especially social determinants of health and their relationship to different parts of the model, to take more effective measures for behavioral stability at the same time as training.